A Study on Trade between China and Central and Eastern European Countries: Does the 16+1 Cooperation Lead to Significant Trade Creation?. Issue 4 (4th July 2021) - Stanojevic, Savo; Qiu, Bin; Chen, Jian
ABSTRACT: This study aims to examine whether the establishment of the 16 + 1 Cooperation between China and Central and Eastern European countries in 2012 resulted in significant trade creation. For that purpose, we used a theoretically consistent gravity model and a panel dataset consisting of 167 countries and covering the period 2001–2019. The results show a slowdown in Sino-CEEC trade after 2012, indicating that the cooperation has so far not led to significant trade growth. The estimates also indicate that the cooperation could have greater positive effects on China's trade with non-EU CEEC, however, we do not find sufficient evidence for this.